Overview of advances in improving uniformity and water use efficiency of sprinkler irrigation - Darko, Ransford Opoku; Shouqi, Yuan; Junping, Liu; Haofang, Yan; Xingye, Zhu (International Journal of Agricultural and Biological Engineering, 2017)
Water is the scarcest resource and the importance of the judicious use of water in the agricultural sector for sustaining agricultural growth and the retardation of environmental degradation needs no further elaboration. The successes of using sprinkler irrigation to develop new lands, point the way forward to a much greater role for the development of future land reclamation projects. Water use efficiency through a proper improvement of water management techniques and other production factors are essential to boost on-farm productivity. Various factors affecting uniformity and water use efficiency in sprinkler irrigation have been outlined in this research, highlighting possible ways to improve such essential parameters in crop production. The study emphasizes on an irrigation system that works adequately in applying water to stay within the root zone, making the water always available in sufficient quantities to meet the crop water needs. It suggests practical ways of managing irrigation systems within tolerable limits not neglecting the effects of wind which is a major contributing factor to non uniformity in sprinkler irrigation.Keywords: sprinkler irrigation, uniformity, water use efficiency, crop yieldDOI: 10.3965/j.ijabe.20171002.1817Citation: Darko R O, Yuan S Q, Liu J P, Yan H F, Zhu X Y. Overview of advances in improving uniformity and water use efficiency of sprinkler irrigation. Int J Agric & Biol Eng, 2017; 10(2): 1–15.